Development of an Experiential Model Based on Executive Functions to Enhance Rational Thinking Ability for Pre-school Children - Muangthong, Wunwisa; Kaewurai , Wareerat; Onthanee, Angkana (Ratchaphruek Journal, 2023)
The purpose of this research was to develop an experiential model based on executive functions to enhance rational thinking ability for preschool children, which included four steps of research and development as follows: Step 1 study guidelines in providing experiences. Step 2 create, determine, and check the quality of the experiential model and to pilot the model. Step 3 try out the experiential model with the research sample group who were 25 students in Kindergarten. They were selected by simple random sampling, the random unit a classroom. Step 4 study of satisfaction with learning through the experiential model. The research findings were as follows. 1) The experiential guideline, the focus was knowledge and understanding of the teachers about EF brain skills in order to provide experiences that could enhance preschool children’s rational thinking ability. 2) As for the result of the quality check of the experiential model, overall, it was at the highest level. In addition, it was found that the effectiveness index (E.I.) of the experiential model was 60.34%. 3)The experiential model was able to enhance all aspects of rational thinking abilities. The mean score before experience management ( = 8.80) was at a moderate ability level, whereas the mean score after the experience management ( = 12.80) was at a high ability level. After the preschool children learned through the model, they had significantly higher score than before learning at the .01 level. and 4) The preschool children in this study were satisfied with the learning experience at a high level.